Comparative safety of mRNA COVID‐19 vaccines to influenza vaccines: A pharmacovigilance analysis using WHO international database. Issue 3 (8th November 2021) - Kim, Min Seo; Jung, Se Yong; Ahn, Jong Gyun; Park, Se Jin; Shoenfeld, Yehuda; Kronbichler, Andreas; Koyanagi, Ai; Dragioti, Elena; Tizaoui, Kalthoum; Hong, Sung Hwi; Jacob, Louis; Salem, Joe‐Elie; et al.
Abstract: Two messenger RNA (mRNA) vaccines developed by Pfizer‐BioNTech and Moderna are being rolled out. Despite the high volume of emerging evidence regarding adverse events (AEs) associated with the COVID‐19 mRNA vaccines, previous studies have thus far been largely based on the comparison between vaccinated and unvaccinated control, possibly highlighting the AE risks with COVID‐19 mRNA vaccination. Comparing the safety profile of mRNA vaccinated individuals with otherwise vaccinated individuals would enable a more relevant assessment for the safety of mRNA vaccination. We designed a comparative safety study between 18 755 and 27 895 individuals who reported to VigiBase for adverse events following immunization (AEFI) with mRNA COVID‐19 and influenza vaccines, respectively, from January 1, 2020, to January 17, 2021. We employed disproportionality analysis to rapidly detect relevant safety signals and compared comparative risks of a diverse span of AEFIs for the vaccines. The safety profile of novel mRNA vaccines was divergent from that of influenza vaccines. The overall pattern suggested that systematic reactions like chill, myalgia, fatigue were more noticeable with the mRNA COVID‐19 vaccine, while injection site reactogenicity events were more prevalent with the influenza vaccine. Compared to the influenza vaccine, mRNA COVID‐19 vaccines demonstrated a significantly higher risk for a few manageable cardiovascular complications, such as hypertensive crisis (adjusted reporting odds ratio [ROR], 12.72; 95% confidence interval [CI], 2.47–65.54), and supraventricular tachycardia (adjusted ROR, 7.94; 95% CI, 2.62–24.00), but lower risk of neurological complications such as syncope, neuralgia, loss of consciousness, Guillain‐Barre syndrome, gait disturbance, visual impairment, and dyskinesia. This study has not identified significant safety concerns regarding mRNA vaccination in real‐world settings. The overall safety profile patterned a lower risk of serious AEFI following mRNA vaccines compared to influenza vaccines.